2022
DOI: 10.3389/fvets.2022.884733
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Multiple Lineages of PRRSV in Breeding and Growing Swine Farms

Abstract: The detection and co-circulation of multiple variants of porcine reproductive and respiratory syndrome virus (PRRSV) have been observed and reported in swine. However, the potential long-term impact of multiple prevailing PRRSV variants on pig-performance is not yet fully understood. The primary objective of this study was to describe the genetic variation of PRRSV in processing fluid (PF), oral fluid (OF), and tonsil scraping (TS) specimens from five swine farms with different production types and PRRS status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…These results suggested that the PRRSV lineages prevalent in different regions were diverse. Similar to previous investigations [ 17 , 26 ], multiple PRRSV lineages prevalent in one pig farm were also observed, which might contribute to the occurrence of recombination events in the PRRSV genome. In addition, some of the newly identified HP-PRRSV strains in the present study were genetically close to JXA1 and JXA1-P120 strains, which strongly suggests that biosecurity improvement rather than the application of attenuated vaccines should be the priority for PRRS control [ 3 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results suggested that the PRRSV lineages prevalent in different regions were diverse. Similar to previous investigations [ 17 , 26 ], multiple PRRSV lineages prevalent in one pig farm were also observed, which might contribute to the occurrence of recombination events in the PRRSV genome. In addition, some of the newly identified HP-PRRSV strains in the present study were genetically close to JXA1 and JXA1-P120 strains, which strongly suggests that biosecurity improvement rather than the application of attenuated vaccines should be the priority for PRRS control [ 3 ].…”
Section: Discussionsupporting
confidence: 88%
“…More recently, the emergence of NADC34-like strains has attracted widespread attention in China [ 15 , 16 ]. Furthermore, the co-circulation of multiple lineages of PRRSV in one pig farm has been observed [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other studies which focused on a single or on few clusters [ 13 ] or subgroups or lineages [ 14 , 22 , 34 ] or limited to a few farms [ 8 ] our study covered all wild-type clusters found over a 10 year-period at the provincial level. Furthermore, each cluster was described based on its detection in at least one of pig site within a year instead of the number of detections, in order to prevent the influence of repeated sampling of the same strain within a herd during the same year.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term monitoring of PRRSV will be helpful for more comprehensively elucidating the infection situation at commercial fattening pig farms, providing insights of great significance for the prevention and control of PRRSV. The coexistence of multiple PRRSV subtypes has always been a problem faced by the global pig industry [ 29 31 ]. Previous studies have demonstrated that PRRSV-2 has long been considered the predominant species in China, cocirculating with PRRSV-1 [ 11 ].…”
Section: Discussionmentioning
confidence: 99%